Strategi Daya Saing Peningkatan Minat pada Program Studi Manajemen Zakat dan Wakaf - Masykuroh, Ely; Sudrajat, Anton (Nidhomiya: Research Journal of Islamic Philanthropy and Disaster, 2022)
The phenomenon of scarcity of enthusiasts in zakat and waqf management study programs in almost all PTKIN in Indonesia compared to other majors/study programs, - it becomes a necessity for policy makers, especially majors/study programs to try to improve competitiveness by formulating appropriate strategies. The approach in strategy formulation uses multi-criteria analysis (MCA) and is analyzed with the Analytical Hierarchy Process (AHP) based on Porter's theory of competitiveness strategy which includes cost advantage, differentiation, and focus, by taking the research locus at IAIN Ponorogo is a necessity for study program policy makers to strive to increase competitiveness by formulating appropriate strategies. The performance approach in strategy formulation uses multi-criteria analysis (MCA) and analyzed by Analytical Hierarchy Process (AHP). The results of this study offer alternative strategies to improve the competitiveness of zakat and waqf management study programs, namely cost advantages, differentiation, and focus where each strategy has advantages and disadvantages. However, the right alternative form of strategy is differentiation. Adanya fenomena kelangkaan peminat jurusan/program studi manajemen zakat dan wakaf di hampir seluruh PTKIN di Indonesia dibandingkan dengan jurusan/program studi yang lain, - menjadi suatu keniscayaan bagi pemangku kebijakan, khususnya jurusan/program studi untuk berupaya meningkatkan daya saing dengan cara merumuskan strategi-strategi yang tepat. Pendekatan dalam penyusunan strategi menggunakan analisis multi kriteria (MCA) dan dianalisis dengan Analytical Hierarchy Process (AHP) dengan berpijak dari teori strategi daya saing Porter yang meliputi keunggulan biaya, diferensiasi, dan focus dengan mengambil lokus penelitian di IAIN Ponorogo. Hasil penelitian ini menawarkan alternatif strategi untuk meningkatkan daya saing program studi manajemen zakat dan wakaf melalui keunggulan biaya, diferensiasi, dan fokus dimana masing-masing strategi memiliki kelebihan dan kekurangan. Namun, bentuk alternatif strategi yang tepat pada saat ini adalah diferensiasi.